Intelligence, Aptitude, Motivation, Support, Opportunity, Readiness, and Interest (IAMSORI) Affecting Students in Learning English - Telaumbanua, Yasminar Amaerita; Fauzan, Akhmad (Journal of English Language and Education, 2025)
The goal of this research is to identify the main factor that influences students when learning English. A survey was conducted with 57 students from the English Education Study Program at the University of Nias participating. Data was gathered using a questionnaire on Google Form that employed a Likert scale, and it was analyzed statistically to obtain descriptive statistics and Pearson Correlation results. The results reveal that intelligence shows a perfect positive correlation in sig. (2-tailed) with all factors at levels of 0.01 and 0.05. It has an unstandardized coefficient (B) of 4.439 and a standard error of 0.657, culminating in a t-value of 6.761. The significance level of intelligence is below 0.001, suggesting that it is an extremely important part of the model. The conclusion of the research indicates that intelligence is the primary factor among all the influences on students in learning English, as determined by Beta Coefficient.